The Human Factor In Structural Failures: Errors During Design and Construction - Idrus, Ir. Arazi (Lembaga Jurutera Malaysia, 1995)
Many investigations carried out across the world in examining the events that caused tructural failures revealed that a majority occurred as a result of human errors, particularly those occurring during design and construction. A literature study is presented and aimed at reviewing the current state pf knowledge concerning human errors that may lead to structural failures in terms of their detection, caused, sources, consequences and general characteristics. From this study, it is concluded that errors cannot be eliminated simply by adopting a higher factor of safety or imposing a more comprehensive qualtiy control programme. They can only be mitigated and controlled by adpting scertain strategies based on a probabilistic approach. These strategies, as proposed, are aimed at reducing their occurrences as well as reducing their impact on structural performance.